THE GOODNESS OF LONG PATH WITH RESPECT TO MULTIPLE COPIES OF COMPLETE GRAPHS - Sudarsana, I Wayan (Journal of the Indonesian Mathematical Society, 2014)
Abstract PDF DOI : http://dx.doi.org/10.22342/jims.20.1.179.31-35